2017
DOI: 10.1016/j.otsr.2017.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Giant cell tumor of tendon sheath: Open surgery or arthroscopic synovectomy? A systematic review of the literature

Abstract: Review of literature, level of evidence IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 63 publications
0
36
0
4
Order By: Relevance
“…Synovectomies were mostly performed open. To date, literature reported con icting results regarding different surgical techniques, not favoring one over another [15,32,33]. However, we hypothesize that open surgery may allow for better overview of tumor, located intra-and extra-articular, with extension to surrounding tissues, possibly resulting in more complete removal of disease burden.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Synovectomies were mostly performed open. To date, literature reported con icting results regarding different surgical techniques, not favoring one over another [15,32,33]. However, we hypothesize that open surgery may allow for better overview of tumor, located intra-and extra-articular, with extension to surrounding tissues, possibly resulting in more complete removal of disease burden.…”
Section: Discussionmentioning
confidence: 87%
“…TOPP represents the largest prospective, international, multi-center disease registry for dt-TGCT, being able to include 166 patients in slightly more than 2 years, and shows that conducting collaborative observational studies for rare tumor is feasible. Current literature is largely focused on the oncological outcomes of this often chronic disease [15,16,17,18,19,20,21,22]. Data derived from this registry made it possible for the rst time to describe the dt-TGCT patient journey and treatment decisions around disease onset and diagnosis of dt-TGCT patients.…”
Section: Discussionmentioning
confidence: 99%
“…Though Dt-GCT is usually managed with open synovectomy, while arthroscopic synovectomy is usually indicated in localized GCT, no consensus about the treatment strategies has been reached. Most recently, Noailles T and his colleagues [ 32 ] reviewed the literature about open surgery or arthroscopic synovectomy for GCT-TS in 2017, 33 articles were selected in this review, involving 1448 individuals. They concluded that arthroscopic excision was effective for localized GCT-TS for all four joints (shoulder, hip, knee, ankle).…”
Section: Discussionmentioning
confidence: 99%
“…TKDHT'nin tedavisi eklem destrüksiyonunu sınırlamak için erken dönemde yapılan cerrahi eksizyondur. 1 Total eksizyon, tümörün tedavisini ve nüks riskinin azaltılmasını sağlamaktadır. Prognozu iyidir ama rekürens riski yüksektir.…”
Section: Parmakta Travma Sonrasıunclassified